2011
DOI: 10.1371/journal.pone.0026659
|View full text |Cite
|
Sign up to set email alerts
|

Operational Challenges in Diagnosing Multi-Drug Resistant TB and Initiating Treatment in Andhra Pradesh, India

Abstract: BackgroundRevised National TB Control Programme (RNTCP), Andhra Pradesh, India. There is limited information on whether MDR-TB suspects are identified, undergo diagnostic assessment and are initiated on treatment according to the programme guidelines.ObjectivesTo assess i) using the programme definition, the number and proportion of MDR-TB suspects in a large cohort of TB patients on first-line treatment under RNTCP ii) the proportion of these MDR-TB suspects who underwent diagnosis for MDR-TB and iii) the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
50
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 1 publication
0
50
1
Order By: Relevance
“…6 A study in China showed that less than one third of patients who should have undergone CDST actually did so. 4 In India, only 55% of MDR-TB suspects had positive culture results, 5 and in a recent study in presumptive MDR-TB patients in Cambodia, less than 50% were examined for culture and only 21% had positive M. tuberculosis cultures. 15 How do we begin to improve the system?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 A study in China showed that less than one third of patients who should have undergone CDST actually did so. 4 In India, only 55% of MDR-TB suspects had positive culture results, 5 and in a recent study in presumptive MDR-TB patients in Cambodia, less than 50% were examined for culture and only 21% had positive M. tuberculosis cultures. 15 How do we begin to improve the system?…”
Section: Discussionmentioning
confidence: 99%
“…The logistics of getting sputum samples to a central reference laboratory (CRL), as is the case in Nepal, is not easy, and this has proved difficult in other countries. [3][4][5][6] We therefore carried out a retrospective study to determine how the CDST process worked among retreatment patients in the mid-west region of Nepal, the results of CDST when specimens did successfully reach the CRL, and the time taken for all procedures to be performed.…”
mentioning
confidence: 99%
“…Under Revised National TB Control Programme (RNTCP), we have one designated microscopy centre (DMC) for every 100,000 population [22]. These DMCs are responsible for detection of all the new TB cases and hence the improvement in case detection is directly related with the improvement in microscopy.…”
Section: Discussion:-mentioning
confidence: 99%
“…First, about 10% of patients with presumptive MDR-TB were not identified or referred for testing, an aspect missed by most of the other studies on this issue, and similar to an existing study from Andhra Pradesh, India. 9 Attrition at this stage was mainly seen among previously treated patients with EPTB (categorised as 'retreatment others'). This was predominantly due to a lack of clarity among the programme staff with respect to whether EPTB patients need to be referred.…”
Section: Discussionmentioning
confidence: 99%
“…2 Studies from around the world have raised concerns over the high pre-diagnostic and pre-treatment attrition in MDR-TB diagnosis and treatment pathways (DTP). [3][4][5][6][7][8][9] Most of these studies were conducted in settings with the capacity for phenotypic diagnostic techniques, with a long turnaround time (TAT). A study from New Delhi, India, identified a significant decrease in TAT and pre-treatment loss to follow-up in 2014 after the introduction of line probe assay (LPA) technology, mainly attributed to a decrease in laboratory diagnostic time, although other operational issues were still of concern.…”
mentioning
confidence: 99%